2016
DOI: 10.1158/1535-7163.mct-15-0344
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Photodynamic Virotherapy Armed with a Genetically Encoded Photosensitizer

Abstract: Photodynamic therapy (PDT) is a minimally invasive antitumor therapy that eradicates tumor cells through a photosensitizermediated cytotoxic effect upon light irradiation. However, systemic administration of photosensitizer often makes it difficult to avoid a photosensitive adverse effect. The red fluorescent protein KillerRed generates reactive oxygen species (ROS) upon green light irradiation. Here, we show the therapeutic potential of a novel tumor-specific replicating photodynamic viral agent (TelomeKiller… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 30 publications
0
23
0
2
Order By: Relevance
“…274, 278-280 On the other hand, reducing irradiance and/or fluence can achieve sub-lethal levels of ROS for mediating subtle cellular signaling. 277 The first developed RGP was the KillerRed, a homolog of GFP, anm2CP, by Lukyanov and coworkers.…”
Section: Genetically Encoded Photosensitizersmentioning
confidence: 99%
“…274, 278-280 On the other hand, reducing irradiance and/or fluence can achieve sub-lethal levels of ROS for mediating subtle cellular signaling. 277 The first developed RGP was the KillerRed, a homolog of GFP, anm2CP, by Lukyanov and coworkers.…”
Section: Genetically Encoded Photosensitizersmentioning
confidence: 99%
“…A telomerase-specific conditionally Killer-Redexpressing adenovirus has some advantages compared with conventional PDT: (a) the high tumor selectivity and prolonged accumulation of Killer-Red, which is achieved by using a telomerase-specific replicating adenovirus; (b) the dual effects mediated by Killer-Red-mediated cell death as well as virus-mediated cell death. 14 Since light in the yellow-green to orange wavelength range for excitation of Killer-Red has limited depth penetration, 8 cutaneous melanoma can be a good indication for Killer-Red-based PDT. We previously reported that intra-tumor injection of a telomerase-specific replication-competent adenovirus (OBP-301) eliminated lymph node metastasis of an orthotopic colorectal cancer model.…”
Section: Resultsmentioning
confidence: 99%
“…Another marker, KillerRed protein, is one of the brightest red fluorescent proteins, and is excited by a green laser with higher tissue-penetration ability [92]. We have generated a KillerRed-expressing oncolytic adenovirus, TelomeKiller, that permits the selective visualization of a variety of tumor cells, including sarcoma cells [93,94]. TelomeKiller may be a useful reagent for illuminating deep tumor tissues in FGS.…”
Section: Fluorescence-guided Surgery Using the Obp-401-based Gfp Indumentioning
confidence: 99%